Botulinum Toxin: Techniques Within Pediatric Physiatry. Issue 1 (22nd January 2019) - Paulson, Andrea; Zigler, Christina K.; Houtrow, Amy; Pruitt, David
Abstract : Background: Intramuscular botulinum toxin injections are used for treatment of focal spasticity in children, particularly in those with a diagnosis of cerebral palsy. There are a variety of techniques used when performing botulinum toxin injections without clear standards for pediatric providers. Objective: To describe current practice techniques for botulinum toxin injections among pediatric physiatrists. Design: Cross‐sectional survey using RedCap Software. Setting: Pediatric physiatrists who perform botulinum toxin injections. Participants: Survey of 307 pediatric physiatrists. Methods: Analysis of data from the 2017 practice survey of pediatric physiatrists in the United States. Main Outcome Measurements: Physicians were asked the primary botulinum toxin used, common dosing information, the role of localization, and the role of sedation and distraction in their practice. Results: Nearly all pediatric physiatrists use OnabotulinumtoxinA as the primary formulation of botulinum toxin. The maximum dose per body weight used per injection series had a median of 15 units/kilogram and a median maximum total dose of 500 units. Sixty‐five percent of pediatric physiatrists report using sedation, of any type, for botulinum toxin injections. When using sedation, the most common primary method was general anesthesia (38.9%), followed by enteral or nasal anxiolytic with the patient awake (26.2%). The most common reported intended injection site for botulinum toxin was "in multiple sites spread throughout the muscle" (67.9%), and then "one site of the muscle at the motor point" (17.1%). Large muscles were injected using primarily anatomic guidance (75.6%) and electromyography (50.8%), and small muscles were primarily completed with electromyography (73.6%) and anatomic guidance (49.2%). Conclusion: There is considerable variability present in one common procedure performed by pediatric physiatrists. Level of Evidence: NA.